2006
DOI: 10.1523/jneurosci.5270-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Ipsilateral Input Modifies the Primary Somatosensory Cortex Response to Contralateral Skin Flutter

Abstract: We recorded the optical intrinsic signal response of squirrel monkey primary somatosensory cortex (SI) to 25 Hz vibrotactile ("flutter") stimulation applied independently to the thenar eminence on each hand and also to bilateral (simultaneous) stimulation of both thenars. The following observations were obtained in every subject (n ϭ 5). (1) Ipsilateral stimulation was accompanied by an increase in absorbance within the SI hand region substantially smaller than the absorbance increase evoked by contralateral s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
43
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 36 publications
4
43
1
Order By: Relevance
“…the secondary somatosensory cortex (Frot and Mauguière, 1999;Hari et al, 1984) -has been suggested to receive and integrate information from both sides of the body (Desmedt and Robertson, 1977;Eickhoff et al, 2010) via transcallosal connections between homologous SII regions that allow inputs from a stimulated body part to reach the ipsilateral SII area (Schnitzler et al, 1995;Tamè et al, 2015b;Tommerdahl et al, 2006). Additionally, the P100 component has been shown to be the first SEP component integrating contralateral and ipsilateral tactile processing .…”
Section: Visuo-tactile Vs Tactile-tactile Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…the secondary somatosensory cortex (Frot and Mauguière, 1999;Hari et al, 1984) -has been suggested to receive and integrate information from both sides of the body (Desmedt and Robertson, 1977;Eickhoff et al, 2010) via transcallosal connections between homologous SII regions that allow inputs from a stimulated body part to reach the ipsilateral SII area (Schnitzler et al, 1995;Tamè et al, 2015b;Tommerdahl et al, 2006). Additionally, the P100 component has been shown to be the first SEP component integrating contralateral and ipsilateral tactile processing .…”
Section: Visuo-tactile Vs Tactile-tactile Effectsmentioning
confidence: 99%
“…The two suggested alternative explanations are not mutually exclusive and we could speculate that reorganization of somatosensory areas can result by a combination of bottom-up and top-down projections. However, it is worth noticing that, despite bilateral integration of tactile information being generally accepted for structures beyond SI -in particular SII (Eickhoff et al, 2010) -growing evidence has demonstrated contribution of SI in the integration of somatosensory inputs from the 25 two sides of the body (Tamè et al, 2012(Tamè et al, , 2011Tommerdahl et al, 2006).…”
Section: Visuo-tactile Vs Tactile-tactile Effectsmentioning
confidence: 99%
“…However, the hypothesis that SI cortex also receives input from the ipsilateral hand dates back several decades (Tamura, 1972). The responsiveness of ipsilateral SI to distal upper-limb stimulation is supported by converging evidence from multiple lines of research, including the following: (1) cortical ablation studies in rats; (2) single-neuron electrophysiology and functional magnetic resonance imaging (fMRI) with nonhuman primates; and (3) intracranial recording, magnetoencephalographic (MEG), transcranial magnetic stimulation, and fMRI studies with humans, as well as behavioral results from bimanual tasks (for most recent discussion, see Tommerdahl et al, 2006). Despite this evidence, general acceptance has not been achieved, potentially because of the incomplete characterization of ipsilateral input within SI cortex.…”
mentioning
confidence: 99%
“…Three possibilities have been considered: (1) transcallosal input from contralateral SI (Allison et al, 1989); (2) direct uncrossed afferent projections to ipsilateral SI (Kanno et al, 2003); and (3) top-down input from higher-level processing areas such as SII (Tommerdahl et al, 2006). Hlushchuk and Hari (2006) suggest that the observed ipsilateral responses result from transcallosal input.…”
mentioning
confidence: 99%
See 1 more Smart Citation